(untitled) (International Journal of Engineering and Computer Science, 2024)
This main objective of the present study is to analyse profit analysis of a Rubber Roller in hulling system used in rice-mill with change in demand of Rice. We consider two type of upstate when demand is more than or equal to supply and Supply is more than demand. When there is less demand or supply is more than demand the operative unit put in down state. preventive maintenance (PM) carried on during downtime There is a single server who visits the system immediately whenever needed to carry out preventive maintenance and repair. The analysis incorporates the Weibull distribution to model the failure and repair times of the hulling system components, Using semi Markov process and regenerative point techniques various reliability characteristics are obtained.